2012
DOI: 10.1159/000337954
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Grand Rounds: Atypical Hemolytic Uremic Syndrome

Abstract: Atypical hemolytic uremic syndrome (aHUS) is a rare, lifethreatening, chronic, genetic disease of uncontrolled alternative pathway complement activation. The understanding of the pathophysiology and genetics of this disease has expanded over recent decades and promising new developments in the management of aHUS have emerged. Regardless of the cause of aHUS, with or without a demonstrated mutation or autoantibody, blockade of terminal complement activation through C5 is of high interest as a mechanism to ameli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 54 publications
0
17
0
Order By: Relevance
“…Most of the 17 patients treated for post-transplant recurrence outside of prospective trials were adults who carried high-risk mutations and/or had lost prior grafts due to recurrence [71,73,[94][95][96]. Shorter interval between the onset of recurrence and treatment initiation was correlated with greater gain of graft function [71].…”
Section: Case Reports Of Eculizumab To Treat or Prevent Post-transplamentioning
confidence: 99%
“…Most of the 17 patients treated for post-transplant recurrence outside of prospective trials were adults who carried high-risk mutations and/or had lost prior grafts due to recurrence [71,73,[94][95][96]. Shorter interval between the onset of recurrence and treatment initiation was correlated with greater gain of graft function [71].…”
Section: Case Reports Of Eculizumab To Treat or Prevent Post-transplamentioning
confidence: 99%
“…A randomized controlled clinical trial of eculizumab in 37 adults with aHUS showed resolution of TMA, thrombocytopenia, and return of kidney function [9]. As supported by this case report, eculizumab appears to be especially effective in recurrent TMA post-transplant [5, 10, 11]. Treatment with C5 inhibition may also be efficacious in patients with aHUS who have received a long course of dialysis prior to eculizumab treatment [12].…”
Section: Discussionmentioning
confidence: 84%
“…C5b initiates the assembly of the MAC, leading to undesirable membrane injury, while C5a recruits and activates leukocytes and upregulates vascular adhesiveness. The delicate balance between complement activation and regulation is thus disturbed on endothelial cells, resulting in a TMA (13, 14). …”
Section: Hemolytic Uremic Syndromementioning
confidence: 99%